Answer:
3t+2
Step-by-step explanation:
First, we focus on the part with the "t" variable. Then we subtract the values with variables which gets us 3t. Finally, we can't do anything with the +2, so our solution is 3t+2.
54 can be factored as follows:
54
2*27
2*3*9
2*3^2*3
2*3^3
Therefore, 54 is equal to 2*3^3, or 2*3*3*3.
Answer:
Step 1: Simplify both sides of the equation.
6(3x−5)−7x=25
(6)(3x)+(6)(−5)+−7x=25(Distribute)
18x+−30+−7x=25
(18x+−7x)+(−30)=25(Combine Like Terms)
11x+−30=25
11x−30=25
Step 2: Add 30 to both sides.
11x−30+30=25+30
11x=55
Step 3: Divide both sides by 11.
x=5
Step-by-step explanation:
Answer:
I think its 55
Step-by-step explanation: